2019
DOI: 10.1093/biolinnean/blz020
|View full text |Cite
|
Sign up to set email alerts
|

Do structural habitat modifications associated with urbanization influence locomotor performance and limb kinematics in Anolis lizards?

Abstract: Urbanization significantly alters habitats for arboreal species, increasing the frequency of very smooth substrates by substituting artificial objects, such as metal poles and painted walls, for some trees. Because they experience these novel substrates more often, urban animals may use strategies to overcome challenges from substrate smoothness that animals from natural habitats do not. We assessed locomotor performance and two-dimensional hindlimb kinematics of two species of Anolis lizards (Anolis cristatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 61 publications
(80 reference statements)
0
5
0
Order By: Relevance
“… Winchell et al (2018b) found that lizards with larger toepads and more lamellae outperformed those with smaller toepads and fewer lamellae on smooth surfaces where claws were likely ineffective. Toepads likely enhance locomotor performance on these surfaces by reducing loss of traction and aid in counteracting the backward pitching effect generated by longer limbs when climbing vertical surfaces ( Kolbe et al 2015 ; Winchell et al 2018b ; Battles, Irschick & Kolbe 2019 ; Naylor & Higham 2019 ). These phenotypic shifts have likely conferred a performance advantage to urban A. cristatellus , particularly on smooth vertical substrates such as painted walls and fences common to urban environments ( Winchell et al 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“… Winchell et al (2018b) found that lizards with larger toepads and more lamellae outperformed those with smaller toepads and fewer lamellae on smooth surfaces where claws were likely ineffective. Toepads likely enhance locomotor performance on these surfaces by reducing loss of traction and aid in counteracting the backward pitching effect generated by longer limbs when climbing vertical surfaces ( Kolbe et al 2015 ; Winchell et al 2018b ; Battles, Irschick & Kolbe 2019 ; Naylor & Higham 2019 ). These phenotypic shifts have likely conferred a performance advantage to urban A. cristatellus , particularly on smooth vertical substrates such as painted walls and fences common to urban environments ( Winchell et al 2018b ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the running speed of light lizards on the melanistic substrate is higher than that on the non-melanistic substrate, indicating that light lizards face greater predation pressure in noncamouflaged environments. We also predicted that this result would be partially correlated with different types of surfaces (Battles et al, 2019;Bergmann et al, 2017;Irschick & Losos, 1999;Kolbe et al, 2016;Li et al, 2011). One possibility is that unsuccessful camouflage on the melanistic substrate may force light lizards to run faster.…”
Section: Discussionmentioning
confidence: 85%
“…As most adhesive and locomotor performance studies are conducted in the laboratory on smooth, artificial substrates, it is difficult to predict if and how gecko adhesion on rough substrates will influence locomotor performance. Work on adhesive pad‐bearing anoles shows that urbanization and the increase in smooth, artificial substrates in the environment result in variation in morphology, performance, and behavior (Battles et al, 2018, 2019; Kolbe et al, 2016; Winchell et al, 2016). This result may also occur in geckos, especially those inhabiting urban areas.…”
Section: Discussionmentioning
confidence: 99%